Prognostic Value and Immune Landscapes of m5C-Related lncRNAs in Lung Squamous Cell Carcinoma - Xu, Ruoxin; Zhang, Wenxiong (Frontiers in Genetics, 2022)
5-methylcytosine (m5C) modification is involved in the tumor progression. However, the lncRNAs associated with m5C in lung squamous cell carcinoma (LUSC) have not been elucidated. The Cancer Genome Atlas database was used to get the open-accessed transcriptional profiling and clinical information of LUSC patients. All the statistical analysis were performed based on R software v 4.0.0 and SPSS13.0. Firstly, there were 614 m5C-related lncRNAs were identified under the criterion of |R|>0.4 and p<0.001 with m5C genes. Next, a prognosis model based on ERICD, AL021068.1, LINC01341, AC254562.3 and AP002360.1 was established, which showed a good prediction efficiency in both training and validation cohorts. Next, a nomogram plot was established by combining the riskscore and clinical features for a better application in clinical. Pathway enrichment analysis showed that the pathways of angiogenesis, TGF-β signaling, IL6-JAK-STAT3 signaling, protein secretion, androgen response, interferon-α response and unfolded protein response were significantly enriched in the high-risk patients. Immune infiltration analysis showed that riskscore was positively correlated with neutrophils, resting CD4+ memory T cells, M2 macrophages, yet negatively correlated with follicular helper T cells, CD8+ T cells and activated NK cells. Moreover, we found that high-risk patients might be more sensitive to immunotherapy, imatinib, yet resistant to erlotinib, gefitinib and vinorelbine. In summary, our prognosis model is an effective tool that could robustly predict LUSC patients prognosis, which had the potential for clinical guidance.